Pendampingan Kelompok Wanita Tani Rahayu di Era Less Contact Economy - Yohanes Anton Nugroho; Ari Zaqi Al Faritsy; Ari Sugiharto (Jurnal ABDI RAKYAT, 2024)
The occurrence of the Covid 19 pandemic and followed by restrictions on people’s activities caused a decrease in sales turnover for Kelompok Wanita Tani (KWT) Rahayu. Tempe sales had experienced a decline of up to 50%, as well as a decrease in processed products made from tempe. Reducing community activities requires a breakthrough to survive in the era of less economic contact. This community service program is carried out to provide socialization and assistance related to the development of online marketing, e-commerce, and the development of packaging that is acceptable to the market.